Using Artificial Intelligence to Set Information Free - McAfee, Reid Hoffman. Clayton Christensen M. Michael Schrage. Vijay Govindarajan. Erik Brynjolfsson. Rita McGrath Gunther. Lynda Gratton. Julian Birkinshaw. Pankaj Ghemawat. Douglas Ready A. Andrew (MIT Sloan Management Review, 2016)
Artificial Intelligence is about to transform management from an art into a combination of art and science. Not because we'll be taking commands from science fiction's robot overlords, but because specialized AI will allow us to apply data science to our human interactions at work in a way that earlier theorists like Peter Drucker could only imagine.